Effect of Air Pollution and Hospital Admission: A Systematic Review - Norfazillah Ab Manan (Ubiquity Press, 2018)
Introduction Many epidemiological studies have demonstrated associations between air pollution levels and human health in terms of hospital admissions. The aim of this paper is to gather evidence concerning air pollution effects on the risk of hospital admission. We hypothesised that increase in: particulate matter (PM), ozone (O3), carbon monoxide (CO), nitrogen dioxide (NO2), and sulphur dioxide (SO2) levels would be associated with the increasing trend of hospital admission. Methods A systematic review of literature was carried out. Literature search was done in Sage, Ovid Medline, Science Direct, Wiley and ProQuest from 2010 to 2016 using keywords “hospital admission and air pollution”. Studies of any relevant design were included if they presented original data, included at least one analysis where hospital admission was the specific outcome, and one or more of the following exposures were investigated: PM, O3, CO, NO2 and SO2. Results A total of 175 potential studies were identified by the search. Twenty two studies qualified for the review. Air pollution was noted to have an excessive risk of 3.46 (95%CI, 1.67, 5.27) of total hospital admissions. Cardiovascular admission was noted to have an increased risk of hospitalization for PM2.5 of 1.5 to 2.0; PM10 (1.007 to 2.7); NO2 (1.04 to 1.17) and SO2 (1.007). For respiratory admission, PM2.5 can caused an increased risk of hospitalization by 1.1 to 1.8; PM10 (1.007 to 1.13); NO2 (1.08 to 1.94) and SO2 (1.02). While O3 have minimal effect on COPD and stroke, CO does not influence in the effect of these hospitalization. Conclusion The exposure to air pollutants confers an increased risk of admission of several disease. Our findings call for greater awareness of environmental protection and the implementation of effective measures to improve the quality of air, which may reduce the risks of adverse effects on the population’s health.